Sample preparation methods for pesticides analysis in food matrices and environmental samples by chromatography-based techniques: a review - Sobhanzadeh, E.; Bakar, N.K.A.; Abas, M.R.; Nemati, K. (2009)
Much attention has been made in pesticide analysis to improve agricultural productivity and control these compounds in food and environmental samples. Different methods have been applied in pesticide analysis, among these; methods based on chromatographic separation with mass spectrometric detection have been extremely useful methods for determination of pesticide residues. Despite employing of powerful instrumental techniques, the risk of interference increases with the complexity of the matrix studied, so sample preparation prior to instrumental analysis is necessary. This article reviews the analytical characteristics of the different sample preparation methods for determination of pesticide residues in food and environmental samples and biological fluids, moreover this study describes advantages, disadvantages and details on the analytical characteristics of the procedure that have been applied recently in different sample preparation methods and their application s in combination with chromatographic mass spectrometric analysis. This article provides selection of a reliable method which will be useful for the quantitative analysis of pesticide residues in variety of samples based on their evaluation in recent applications.